TECHNIQUES USED IN TRANSLATING MORAL AND RELIGION VALUES IN THE RAINBOW TROOPS - Cucu Mariam; Yanti Suryanti (Pedagogia: Jurnal Ilmiah Pendidikan, 2021)
The aims of this research is to find out the techniques that are used in translating the moral and religion values in literary text. The data of this research are taken from Laskar Pelangi and its translation The Rainbow Troops written by Andrea Hirata. The method used is content analysis with qualitative approach. The result of the research is that the moral values that are mostly found are hardworking and love; the religion values are loving Allah by doing all His command; and the techniques that are mostly used are free translation, substitution and omission. Although there are several sentences and content are omitted, the meaning and the values are still delivered completely to the readers.